THE EFFECT OF AROMATHERAPY ROSE TOWARD DECREASE OF ANXIETY IN PATIENTS PRE-OPERATIVE MAJOR SURGERY IN WALED PUBLIC HOSPITAL CIREBON - Nur Kholifah; Dewi Erna Marisa; Sumarni (LPPM ITEKES Mahardika, 2019)
Major surgical operations each year increase. The design used was quasy experiment with pre-post control group design approach. With incidental sampling technique. The number of samples of 30 respondents. The convenience instrument used is an observation sheet that refers to the APAIS questionnaire and analyzed by Paired t-test. This research carried out in the anggrek ward, bougenvill male and female of Waled Public Hospital Cirebon in June-July 2018.Result of univariate analysis, anxiety in patients pre-operative mayor suergery after intervention was (12,000) with standard deviation 4,32600 and lowest comfort was 6,00 and highest comfort was 20,00. Bivariate analysis with paired t-test showed that there was influence of aromatherapy rose toward decrease of anxiety in patiens pre-operative major surgery (p-value = 0,000 α = 0,05).